Comparative Study of Two Different Techniques for Management of Dry Socket - Kansakar, N; Mahendra, H; Acharya, S (Journal of Nepalgunj Medical College, 2015)
Background: Dry socket is the most common post-operative complication following extraction of teeth. Various risk factors have been mentioned for this complication including gender, age, amount of trauma during extraction, difficulty of surgery, inappropriate irrigation, infection, smoking, and oral contraceptive use. Traditional treatment of dry socket require frequent visit of patient to the dental hospital and is very inconvenient to the patient. Objective: The aim of the study was to assess outcome of the treatment using two different techniques for the management of dry socket. Methods: Patients with dry socket were randomly distributed among two treatment groups (21 patients in each group). Group A received irrigation of socket with diluted hydrogen peroxide and zinc oxide eugenol dressing was given and patients were followed for following consecutive days by replacing dressing each day until the pain subsides. Group B received irrigation of socket with diluted hydrogen peroxide, sockets and surrounding gingival tissue were debrided to promote the re-establishment of blood clot. The gingival margins were meticulously sutured to protect the clot formation. Result 19 patients out of 21 in Group A, received two or more than two procedures to subside pain whereas in Group B, 19 out of 21 patients received just one procedure for successful treatment. Concusion: There is reduction in duration of treatment in debridement group of patients when compared with those treated traditionally. Journal of Nepalgunj Medical College Vol.12(1) 2014: 6-9